The last battle / The chronicles of narnia - Lewis, C.S. 1898-1963. (London HarperCollins, 2015)
Lucy and Edmund, accompanied by their peevish cousin Eustace, sail to the land of Narnia where Eustace is temporarily transformed into a green dragon because of his selfish behavior and skepticism.
Q
b
b
Keywords: fantasy